1998
DOI: 10.1007/s002510050395
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions.

Abstract: HLA-DRB6 is one of the human major histocompatibility complex (MHC) genes present in DR1, DR2, and DR10 haplotypes (approximately 26% of individuals). It shows several anomalies in human and non-human primates, including exon 2 stop codons (non-randomly grouped between codons 74 and 94) and a promoter region, and an exon 1 coming from an inserted retrovirus. It has been shown that not only chimpanzee but also human Mhc-DRB6 lack the usual 3' untranslated (UT) polyadenylation signal, and in the present work it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…2; PS signifies pseudogenes with a frameshift, N signifies the presence of genomic sequences, where no cDNA sequences were found). Pseudogene Meme-MHC I*PS04N was detected only in gDNA, whereas Meme-MHC I*PS01 , Meme-MHC I*PS02 , and Meme-MHC I*PS03 were only detected in the cDNA, indicating the presence of a transcribed nonfunctional pseudogene (Mayer et al 1993; Fernandez-Soria et al 1998). The nucleotide deletion in Meme-MHC I* PS01 and Meme-MHC I*PS03 occurred at the 5′ primer annealing site for exon 2 amplification from gDNA; thus, no sequence was detected from gDNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2; PS signifies pseudogenes with a frameshift, N signifies the presence of genomic sequences, where no cDNA sequences were found). Pseudogene Meme-MHC I*PS04N was detected only in gDNA, whereas Meme-MHC I*PS01 , Meme-MHC I*PS02 , and Meme-MHC I*PS03 were only detected in the cDNA, indicating the presence of a transcribed nonfunctional pseudogene (Mayer et al 1993; Fernandez-Soria et al 1998). The nucleotide deletion in Meme-MHC I* PS01 and Meme-MHC I*PS03 occurred at the 5′ primer annealing site for exon 2 amplification from gDNA; thus, no sequence was detected from gDNA.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that many MHC sequences can be detected at the genomic level, but not at the cDNA level (de Groot et al 2004). The presence of expressed nonfunctional MHC pseudogenes has also been reported (Mayer et al 1993; Fernandez-Soria et al 1998), even in the class II genes of M. meles (Sin et al 2012). This is concordant with the finding that the MHC class I and class II regions have duplicated many times, generating many pseudogenes in addition to novel functional genes (Beck et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Considering the postulated role of MHC-G in preserving the fetus from maternal NK cell attack, and considering that the pregnancies are normal, usually bearing just one fetus, functional MHC-G molecules may exist in these species lacking the α2 domain. Otherwise, the existence of reading-through stop codon mechanisms may be present, as found in certain mammalian genes [102104].
Fig.
…”
Section: Evolution Aspects Of Hla-gmentioning
confidence: 99%
“…This can be explained by the integration of a retroviral insert the long terminal repeat of which provides a promotor and a stretch of hydrophobic amino acids that could function as a leader (36). In addition, transcription and translation of human and chimpanzee -DRB6 genes could be demonstrated (37,38 In the case of HLA-DRB region configurations, the order of genes was determined by genomic mapping (17). In the case of the rhesus macaque, neither the exact order of genes nor whether the lineages represent different loci is known.…”
Section: Conservation Of the Mhc-drb6 Pseudogenementioning
confidence: 99%